Factors affecting the capabilities of family development centre staff regarding promotion of pre-school language learning amongst parents in Thailand - Warunsicha Supprasert; Piyatida Khajornchaikul; Kitiphong Harncharoen; Pimsurang Taechaboonsermsak; Supachai Pitikultang; Udomluck Kulapichitr (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The purpose of this paper is to investigate the factors contributing to the competencies and capabilities of Family Development Center (FDC) staff in order to promote pre-school language developmental support amongst parents. Design/methodology/approach - A cross-sectional study was conducted amongst 260 FDC staff under the supervision of Thai local authorities in the rural province of Suphanburi in Thailand from July to September 2016. Self-administered questionnaires were used. Eligible participants with at least a year's experience on the FDC committee were purposively selected. Analyses were performed by descriptive statistics, Pearson's correlation, Spearman's correlation, χ2 test and stepwise multiple regression. Findings - Only 23.5 percent of staff had a high level of capability. The respondents' perceptions of their self-capability were inﬂuenced by motivation, attitudes toward promoting language learning amongst parents, self-efficacy, sufficient budget and receiving constructive appraisal support (r=0.387, 0.328, 0.366, 0.106 and 0.104, respectively). Marital status was negatively associated with FDC staff capability (r=−0.172). The multivariate analysis showed that 23.9 percent of the variability of FDC staff's self-capability could be explained by their motivation for working, attitude, self-efficacy and marital status (p<0.001). Originality/value - Research findings could be used to improve motivation for working, positive attitudes and self-efficacy regarding parenting promotion for pre-school language development to achieve standardized quality performance. Results of this study could also form the basis for designing effective training programs for FDC staff in the context of the specific organization and community.